Respuesta :

Answer:

x = -6

y = 8

Step-by-step explanation:

Using substitution method.

2x + y = -4 -----------(I)

      y = - 4 - 2x -----------(II)

5x + 3y = -6 -------------------(III)

Substitute y = -4 -2x in equation (III)

5x + 3(-4-2x) = - 6

5x - 12  - 6x = -6

5x - 6x - 12 = -6

Combine like terms

    -x - 12     = -6   {Add 12 to both sides}

              -x = -6 + 12

              -x = 6              {Multiply by (-1)}

               x = -6

Substitute x = -6 in equation (II)

y = - 4 - 2*(-6)

  = -4 + 12

y = 8